2012
DOI: 10.1007/s00284-012-0095-6
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Cloning and Characterization of the Glycerol-3-Phosphate Dehydrogenase (GPDH) Gene Family in the Green Microalga Chlamydomonas reinhardtii

Abstract: Glycerol-3-phosphate dehydrogenase (GPDH) catalyzes the conversion of dihydroxyacetone phosphate (DHAP) and NADH to glycerol-3-phosphate (G3P) and NAD(+). G3P is important as a precursor for glycerol and glycerolipid synthesis in microalgae. A GPDH enzyme has been previously purified from the green microalga Chlamydomonas reinhardtii, however, no genes coding for GPDH have been characterized before. In this study, we report the in silico characterization of three putative GPDH genes from C. reinhardtii: CrGPDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…Those authors also showed that almost no glycerol accumulated under mild osmotic stress (e.g., 50 mM NaCl). In our previous study, we showed that a 200-mM NaCl treatment induced the expressions of CrGPDH2 and CrGPDH3, and in the absence of this treatment, the expression of both genes was barely detectable by end-point PCR (Herrera-Valencia et al 2012). We extended the expression analyses of these genes and found that both CrGPDH2 and CrGPDH3 were induced under all the NaCl treatments tested.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Those authors also showed that almost no glycerol accumulated under mild osmotic stress (e.g., 50 mM NaCl). In our previous study, we showed that a 200-mM NaCl treatment induced the expressions of CrGPDH2 and CrGPDH3, and in the absence of this treatment, the expression of both genes was barely detectable by end-point PCR (Herrera-Valencia et al 2012). We extended the expression analyses of these genes and found that both CrGPDH2 and CrGPDH3 were induced under all the NaCl treatments tested.…”
Section: Discussionmentioning
confidence: 72%
“…Based on in silico characterization, a phylogenetic analysis and an expression analysis, we had previously suggested that CrGPDH2 and CrGPDH3 encode GPDH enzymes that could be involved in glycerol production in response to NaCl stress in C. reinhardtii (Herrera-Valencia et al 2012). In the present study, we have demonstrated that both gene products have GPDH activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations